Intercultural Competence and Pragmatics - Schauer, Gila A. (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This Open Access book examines the link between intercultural competence (IC) and pragmatics by asking frontline modern foreign language teachers in higher education teaching a variety of languages (e.g., Dutch, English, French, German, Italian, Spanish, Swedish) how they conceptualise intercultural competence and which skills, competences and knowledge they consider important in their teaching contexts. The data were collected with an online survey that focused on the relationship between intercultural competence and pragmatics. While international organizations such as the United Nations Educational, Scientific and Cultural Organization (UNESCO) or the Council of Europe (CoE) agree that intercultural competence should play an important role in education, it is not always clear what IC may encompass in specific teaching contexts and subject areas. Examining how modern foreign language teachers in higher education conceptualise intercultural competence and the value they attach as well as the attention they give to various areas of pragmatics in their teaching is highly important, since those language professionals may be the final teachers learners encounter during their formal foreign language education. They are therefore in a unique position to shape modern foreign language learners' intercultural and pragmatic awareness, competence and skills. This book will be of interest to language professionals, modern foreign language teachers and teacher trainers, as well as students and scholars of applied linguistics, pragmatics, and language education. Gila A. Schauer is Professor of English and Applied Linguistics at the University of Erfurt, Germany. She has been researching aspects of intercultural and pragmatic competence for more than 20 years, beginning with her MA and PhD dissertations on cross-cultural and interlanguage pragmatics, then exploring cross-cultural (im)politeness perceptions, young learners and L2 pragmatics, as well as foreign language teachers' views and conceptualisations of intercultural competence. She was Director of the EAP/Study Skills Programme at Lancaster University from 2005 to 2010 and Director of the Language Centre at the University of Erfurt from 2012 to 2014. .